2013
DOI: 10.4161/cc.25451
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a novel regulator of p120 catenin, NLBP, promotes lung adenocarcinoma proliferation

Abstract: NLBP (novel LZAP-binding protein) was recently shown to function as a tumor suppressor capable of inhibiting the NFκB signaling pathway. NLBP is also known as a negative regulator of cell invasion, and its expression is reduced in several cancer cell lines that have little invasive activity. Although these phenomena suggest that NLBP may be a potential tumor suppressor, its role as a tumor suppressor in human lung cancer is not well established. In contrast to our expectation, NLBP was highly expressed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
(50 reference statements)
0
18
0
Order By: Relevance
“…As mentioned in the previous section upon p120-isoform 1, p120-isoforms 1–3 share amino-terminal binding partners including NLBP (Kim et al, 2013), PLEKHA7 (Kurita et al, 2013; Meng et al, 2008; Pulimeno et al, 2010), RPTPµ(Zondag et al, 2000), DIPA (Klompstra et al, 2015; Markham et al, 2012; Markham et al, 2014), and Gα 12 (Ardawatia et al, 2011). While validation remains needed in most cases, the phosphorylation state of the amino-terminal regulatory region is expected to modulate some of these interactions or be a consequence of them, and while a number of phospho-sites currently appear to have lesser functional implications (Mariner et al, 2004), this could change upon applying other assays.…”
Section: Phosphorylation Of P120-cateninmentioning
confidence: 92%
See 1 more Smart Citation
“…As mentioned in the previous section upon p120-isoform 1, p120-isoforms 1–3 share amino-terminal binding partners including NLBP (Kim et al, 2013), PLEKHA7 (Kurita et al, 2013; Meng et al, 2008; Pulimeno et al, 2010), RPTPµ(Zondag et al, 2000), DIPA (Klompstra et al, 2015; Markham et al, 2012; Markham et al, 2014), and Gα 12 (Ardawatia et al, 2011). While validation remains needed in most cases, the phosphorylation state of the amino-terminal regulatory region is expected to modulate some of these interactions or be a consequence of them, and while a number of phospho-sites currently appear to have lesser functional implications (Mariner et al, 2004), this could change upon applying other assays.…”
Section: Phosphorylation Of P120-cateninmentioning
confidence: 92%
“…Recent work has furthermore identified DIPA as a binding partner specific for p120-isoform 1 (Klompstra et al, 2015; Markham et al, 2012; Markham et al, 2014), and an amino-terminal region preceding p120’s coiled-coil domain is an important binding site for kinesin (Figure 1). Given that other proteins associate with p120’s amino-terminal region, such as NLBP, PLEKHA7 and RPTPµ, future tests must assess the isoform specificity of these interactions (Chen et al, 2003; Kim et al, 2013; Kourtidis et al, 2015; Kurita et al, 2013; Markham et al, 2014; Meng et al, 2008; Pulimeno et al, 2010). …”
Section: Phosphorylation Of P120-cateninmentioning
confidence: 99%
“…It is also suggested that Ufm1 is involved in pathological conditions or diseases, such as tumorigenesis (2325), ischemic heart diseases (26) and diabetes (27). Despite, to date, the function of Ufm1 remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…(Strnad et al, 2013; Zatloukal et al, 2007). Importantly, there were a downregulation of Ufmylation in AH, which is important for protein modification and an involvement in various diseases including cancer (Kim et al, 2013; Komatsu et al, 2004; Lemaire et al, 2011), in alcoholic and nonalcoholic steatohepatitis patients, and mice that were fed with DDC (Liu et al, 2014b). We also found a good correlation between the methylation of the promoter region with the transcriptional silencing of Ufmylation in liver biopsies from patients with AH and NASH and that DNMT1 and DNMT3B mRNA levels were significantly upregulated in these biopsies (Liu et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%